Digital filter synthesis based on an algorithm to generate all minimal signed digit representations. - In-Cheol Park (IEEE Transactions on computer-aided design of integrated circuits and systems)
In this paper, the authors propose an algorithm to find all the minimal signed digit (MSD) representations of a constant and present an algorithm to synthesize digital filters based on the MSD representation. The hardware complexity of a digital signal processing system is dependent on the number system used for the implementation. Although the canonical signed digit (CSD) representation is widely employed, as it is unique and guarantees the minimal number of nonzero digits for a constant, the MSD representation provides multiple representations that have the same number of nonzero digits as the CSD representation. The proposed filter synthesis algorithm utilizes this redundancy of the MSD representation to make common subexpressions, as many as possible, leading to smaller filters. By applying the proposed algorithm to the hardware synthesis of finite impulse response filters, the authors obtained multiplier blocks that are 7% smaller than those generated from the CSD representation.